Creating the advertising idea from the view of social learning theory - Rasha Zahran; Abeer Hassan Abdo Mostafa; Faten Ali Ahmed Abo El-Wafa (Journal of Architecture, Art & Humanistic Science, 2023)
Abstract:The research deals with the study of building the advertising idea in light of the concepts of social learning theory so that it can be applied in advertising design. This theory is known by many names such as learning theory by observation and imitation or learning theory by modeling.The design of the advertisement through the mechanisms of social learning allows the formulation of the idea in light of the commutative, cognitive and self-organizing processes, as well as building the idea in light of the targeted learning outcomes from the theory of social learning. For social learning theory, observing and observing the model’s behavior leads to a simulation of the model’s behavior if several factors are available in the person of the model, the observer, and the circumstances.Thus, the design of the advertisement that depends on an advertising persona (the model) according to the theory of social learning, imposes on the designer a set of standards and formulations for the advertising personality to suit the value presented.The research aims to benefit from the concepts of social learning theory to open sources and horizons for formulating advertising ideas that attract the target group. It also aims to determine the types and specifications of the model (advertising personality) and how to employ it to formulate advertising ideas in light of social learning theory. The research follows the descriptive approach accompanied by an analytical and practical study. The research found that the formulation of the advertising idea in light of the targeted learning mechanisms and outcomes from the social learning theory opens up the designer's horizons and perceptions of advertising ideas that achieve the communicative message.